The Role of Imposing Rehabilitation as a Measure for Child Drug Offenses - Irabiah; Muhammad As Ari AM; Anis Ribcalia Septiana; Siti Rahmadanti (Universitas Merdeka Madiun, 2024)
Introduction to the Problem: The importance of rehabilitation in treating addiction among narcotics addicts is crucial to reduce the number of child addicts. However, in practice, there is still an increase in narcotics addiction among children and teenagers. The efficacy of rehabilitation in treating those afflicted by narcotics is crucial, given the inherent challenge faced by victims or users of narcotics in overcoming their dependence on these substances independently. Purpose/Study Objectives: The objective of this research is to understand the fulfillment of children's rights to be protected as offenders of drug misuse, namely their right to avoid detention unless absolutely necessary, which has not been achieved. The purpose of diversion efforts is to protect adolescents involved in drug misuse by preventing their transition from the formal criminal justice system to the informal criminal justice system. Approach research: This research uses a qualitative approach, enabling the researcher to gain an in-depth understanding of how children's rights are fulfilled in the context of narcotics rehabilitation and how the diversion system is applied. This method also allows the researcher to understand the perspectives of stakeholders, such as law enforcement officials, social workers, and the families of children or teenagers involved in drug misuse. Findings: Additional safeguards encompass the oversight, preemptive measures, therapeutic interventions, and reintegration efforts for youngsters engaged in substance misuse. The process of determining rehabilitation as a sanction for perpetrators of narcotics abuse follows the guidelines for granting a determination by a judge to a suspect or accused of narcotics abuse. This determination is made based on a request from National Narcotics Board and investigators, who recommend that victims of narcotics abuse undergo rehabilitation. Paper Type: Research Article